PHYTOCHEMICAL STUDY OF AERIAL PART OF DIFFERENT SPECIES OF ZIZIPHUS GENUS - Singh, Sudhir Kumar; Midha, Anil; Kumar, Umesh (Asian Journal of Pharmaceutical Research and Development, 2017)
The leaves and barks powder are used as aerial part of Ziziphus ziziphus (l) karst and Ziziphus xyloporus, selected from Ziziphus genus were extracted with 95% ethanol for 48 hours through hot percolation method, total alcoholic extract are subjected for different Phytochemical tests for the of presence of secondary metabolites. The phytochemical analysis reveals presence of flavonoids, glycosides, saponins, phenols, lignins, sterols and tannins.